A Managerial Perspective on Learning Organization – The Case of Poland - Agnieszka SKUZA; Habte G. WOLDU; Shawn ALBORZ (Communications of International Proceedings, 2020)
This article aims to uncover the key elements of learning organizations. This goal was achieved through an exploratory study conducted across 79 organizations located in Poland, Central and Eastern Europe's biggest economy. The study used a multi-step approach involving in-depth focus groups and a ranking list sent to participants by e-mail. By identifying four individual-level and five organizational-level categories, the study's outcome offers important insights on how managers perceive learning organizations. The in-depth field study is particularly important due to the recent conceptual confusion about the learning organization concept. This study contributes to academic discussions on learning organizations and offers recommendations that can be applied by companies seeking to expand their operations to Poland and other Central and Eastern European countries.
Keywords: organizational learning; learning organization; knowledge sharing.